2018
DOI: 10.12968/ijtr.2018.25.10.522
|View full text |Cite
|
Sign up to set email alerts
|

Effects and feasibility of virtual reality system vs traditional physical therapy training in multiple sclerosis patients

Abstract: Background/Aims: Traditionally, physical therapy for gait and balance training takes place in a gym setting, which may not fully reproduce situations in everyday activities. The Computer Assisted Rehabilitation ENvironment system provides an immersive virtual environment, allowing a simulation of complex conditions conducive to gait and balance training. The purpose of this study was to determine: (1) the feasibility and safety of using the Computer Assisted Rehabilitation ENvironment system for physical thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Twenty-two articles used the computer-assisted rehabilitation environment system for biomechanical analysis , 15 articles used the computerassisted rehabilitation environment system for rehabilitation [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57], 4 articles were reviews [19,20,58,59] and 9 articles addressed the computerassisted rehabilitation environment system in other ways [60][61][62][63][64][65][66][67][68]. A flow chart summarizing study selection is shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two articles used the computer-assisted rehabilitation environment system for biomechanical analysis , 15 articles used the computerassisted rehabilitation environment system for rehabilitation [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57], 4 articles were reviews [19,20,58,59] and 9 articles addressed the computerassisted rehabilitation environment system in other ways [60][61][62][63][64][65][66][67][68]. A flow chart summarizing study selection is shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Changes from the baseline visit (V 1 ) to month 6 (V 3 ) and from the baseline visit (V 1 ) to month 1 (V 2 ) will be collected as secondary and exploratory variables, respectively. ClinROs were selected on the basis of previous studies of rehabilitation that reported statistically significant improvements by using VRR in disability ( 17 , 18 ), spasms and spasticity ( 40 ), and balance ( 19 , 24 , 33 ).…”
Section: Methodsmentioning
confidence: 99%
“…Virtual reality rehabilitation offers the possibility of task-oriented and home-based training that allows the simulation of complex multisensory situations simulating everyday activities. The use of VR with lifelike scenarios in people with MS has shown to be safe and effective in motor rehabilitation, including gait, balance and arm mobility improvements ( 17 23 ). VRR not only engages patients in motor activities, but it simultaneously require patients to use cognitive abilities, since enriched virtual environments usually require greater attention and dual-tasking to complete the goal-oriented task ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also indicated that task-oriented training is more effective in preserving white matter integrity in the brain than passive training [85]. VR can be used to provide task-oriented training while performing the exercise using a robot [81] and can also improve the experience of therapy as it can motivate and encourage the user during rehabilitation [86]. One of the common drawbacks in studies that have looked at Lokomat and its effect on gait rehabilitation has been the limited size of subject samples [79][80][81].…”
Section: Robot-assisted Gait Training and Rehabilitationmentioning
confidence: 99%